A qualitative study: Understanding the role of intersectoral convergence in the delivery of essential maternal and child nutrition interventions in Odisha, India - Kim, Sunny S.; Avula, Rasmi; Ved, Rajani; Kohli, Neha; Singh, Kavita; van den Bold, Mara; Kadiyala, Suneetha; Menon, Purnima (Springer, 2017)
Background Convergence of sectoral programs is important for scaling up essential maternal and child health and nutrition interventions. In India, these interventions are implemented by two government programs – Integrated Child Development Services (ICDS) and National Rural Health Mission (NRHM). These programs are designed to work together, but there is limited understanding of the nature and extent of coordination in place and needed at the various administrative levels. Our study examined how intersectoral convergence in nutrition programming is operationalized between ICDS and NRHM from the state to village levels in Odisha, and the factors influencing convergence in policy implementation and service delivery. Methods Semi-structured interviews were conducted with state-level stakeholders (n = 12), district (n = 19) and block officials (n = 66), and frontline workers (FLWs, n = 48). Systematic coding and content analysis of transcripts were undertaken to elucidate themes and patterns related to the degree and mechanisms of convergence, types of actions/services, and facilitators and barriers. Results Close collaboration at state level was observed in developing guidelines, planning, and reviewing programs, facilitated by a shared motivation and recognized leadership for coordination. However, the health department was perceived to drive the agenda, and different priorities and little data sharing presented challenges. At the district level, there were joint planning and review meetings, trainings, and data sharing, but poor participation in the intersectoral meetings and limited supervision. While the block level is the hub for planning and supervision, cooperation is limited by the lack of guidelines for coordination, heavy workload, inadequate resources, and poor communication. Strong collaboration among FLWs was facilitated by close interpersonal communication and mutual understanding of roles and responsibilities. Conclusions Congruent or shared priorities and regularity of actions between sectors across all levels will likely improve the quality of coordination, and clear roles and leadership and accountability are imperative. As convergence is a means to achieving effective coverage and delivery of services for improved maternal and child health and nutrition, focus should be on delivering all the essential services to the mother-child dyads through mechanisms that facilitate a continuum of care approach, rather than sectorally-driven, service-specific delivery processes.